2010
DOI: 10.1016/j.contraception.2010.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Self-administration of subcutaneous depot Medroxyprogesterone acetate by adolescent women

Abstract: Background-Intramuscular depot medroxyprogesterone acetate (DMPA-IM) is now available in subcutaneous (SC) formulation, potentially allowing for home-based self-administration. We examined adolescents' interest in and proficiency at DMPA-SC self-administration.Study Design-This is a planned secondary analysis of a randomized controlled trial comparing pain between DMPA-IM and DMPA-SC. In the trial, study participants (N=55) aged 14-21 years were recruited at DMPA initiation and randomized to receive DMPA-IM or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Another study among DMPA-SC clients in Malawi showed that younger self-injectors (18-24 years old) have similar continuity rates with using DMPA-SC compared to older women (21). It had been hypothesized during the roll-out of DMPA-SC in Malawi that the SI option could be a feasible, discreet and convenient option for adolescents, as indicated by studies from other contexts (22)(23)(24), and could even help expand access among adolescents with unmet need for contraceptives. A recent study from Uganda (24) found no significant differences in competence in initial and subsequent SI of DMPA-SC between adolescent self-injectors (aged under 20) and older women, a finding which raises prospects of feasibility of SI among adolescents in similar contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Another study among DMPA-SC clients in Malawi showed that younger self-injectors (18-24 years old) have similar continuity rates with using DMPA-SC compared to older women (21). It had been hypothesized during the roll-out of DMPA-SC in Malawi that the SI option could be a feasible, discreet and convenient option for adolescents, as indicated by studies from other contexts (22)(23)(24), and could even help expand access among adolescents with unmet need for contraceptives. A recent study from Uganda (24) found no significant differences in competence in initial and subsequent SI of DMPA-SC between adolescent self-injectors (aged under 20) and older women, a finding which raises prospects of feasibility of SI among adolescents in similar contexts.…”
Section: Introductionmentioning
confidence: 99%